Rural internet centre (RIC) as a mean for bridging the digital gap in rural communities: Assessment of current situations - Mat Aji, Zahurin; Ibrahim, Huda; Yusop, Nor Iadah; Abd Razak, Rafidah; Sheik Osman, Wan Rozaini (Idea Group Publishing, 2007)
Rural Internet Centre (RIC) project by the Malaysian government offers opportunity to bridge the digital gap between the rural and urban communities in Malaysia. The RIC provides IT skills training and IT awareness programs to all groups of people including women, the elderly, and children. In order to assess the current RIC operations and usage, a survey was conducted in four selected RICs in Kedah and Perlis. Questionnaires were developed to measure the level of RIC usage and the RIC operations in the specific community. The findings show that role of partners, role of administrators, services/activities and functions, objectives, local infrastructures, financial support for sustainability, and users’ trainings and support are critical in the RIC operations. However, this study has identified that applications and content development are also important.